2020
DOI: 10.1111/jcmm.15555
|View full text |Cite
|
Sign up to set email alerts
|

The overexpression of RBM3 alleviates TBI‐induced behaviour impairment and AD‐like tauopathy in mice

Abstract: Alzheimer disease (AD) is the most common form of dementia in older individuals and probably develops as a result of complex interactions among multiple factors, including age, genetics, environment, lifestyle and traumatic brain injury (TBI). 1-5 The evidence has shown that there appears to be a strong link between future risk of Alzheimer's and serious TBI, but how TBI increase future risk of AD is still unclear. 6-8 TBI caused by contact sports, work accident or military blasts may induce acute or potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…40,41 Along those lines, experimental studies with successful viral expression post-injury use a milder severity TBI model. 42,43 There is no clear molecular indicator of why some animals express the AAV whereas a subset does not, although the low number of animals in the nonexpressor group make it di cult to properly conduct statistical analysis. Further investigation of canonical markers of injury severity such as lesion volume, cell damage or neuroin ammatory markers may clarify the role injury severity plays in AAV expression, especially into the subacute and chronic period after TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Along those lines, experimental studies with successful viral expression post-injury use a milder severity TBI model. 42,43 There is no clear molecular indicator of why some animals express the AAV whereas a subset does not, although the low number of animals in the nonexpressor group make it di cult to properly conduct statistical analysis. Further investigation of canonical markers of injury severity such as lesion volume, cell damage or neuroin ammatory markers may clarify the role injury severity plays in AAV expression, especially into the subacute and chronic period after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…A study using a mathematical model to describe CaM protein interactions found that at high calcineurin concentrations, the effect of Ng on CaMKII activation is signi cantly reduced. 42 Although weeks after experimental TBI, calcineurin protein expression is unchanged, activity is signi cantly increased. 14,46 Mathematical models also show that certain concentrations of calcium and CaM increase CaMKII phosphorylation independent of the presence of Ng.…”
Section: Discussionmentioning
confidence: 99%
“…The TXNIP overexpression mouse model was established on day 28 before BCCAO, as described previously [ 26 ]. Briefly, the adeno-associated virus vectors (AAV-TXNIP and AAV-NC) were constructed by Syngentech Co., Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…The benefits of mild hypothermia in reducing brain nerve injury have been confirmed, and this is inseparable from neuroprotection associated with RBM3 under hypothermia (Chip et al, 2011; Choi et al, 2012; Kochanek et al, 2008; Peretti et al, 2015; VanHook, 2017; Zhu et al, 2019). Upregulation of RBM3 induced by hypothermia pretreatment alleviated traumatic brain injury‐induced behavioral damage and Alzheimer's disease‐like tauopathy in mice (Liu et al, 2020). RBM3 provides a beneficial intervention for retinal damage caused by traumatic neuropathy (Rey‐Funes et al, 2017).…”
Section: The Cytoprotection and Neuroprotection Of Rbm3mentioning
confidence: 99%